Uselessness as Main Utilitarian Antivalue of Contemporary Comedic Discourse in English Linguistic Culture - A. I. Bochkarev (Научный диалог, 2023)
The present study examines the features of the comedic objectification of the concept of USELESSNESS in contemporary English-language comedic discourse. This concept is considered for the first time as the main utilitarian antivalue in comedic discourse, using an axiological approach. The analysis includes recordings and scripts of over 70 stand-up comedy performances, more than 500 episodes of various sitcoms, and 60 episodes of different humorous shows. It is determined that within comedic discourse, the concept of USELESSNESS is a socially-oriented antivalue concept. It is noted that the main satirized socio-cultural characteristics are professional traits. It is established that the manifestation of uselessness in English-language comedic discourse is evaluated negatively either by the author of the work or by its positive characters. The main ridiculed characteristics of the antivalue concept of USELESSNESS include failure to perform necessary actions (inability to perform simple / basic actions and low quality of performed actions) and performance of unnecessary actions (actions that bring no benefit; accompanying actions that cause harm). It is determined that police officers, politicians, doctors, military personnel, lawyers, and teachers are most frequently ridiculed. The main linguistic means for expressing the concept of USELESSNESS include hyperbole, paradox, and antithesis.